MENINGKATKAN PRILAKU PERCAYA DIRI ANAK TUNADAKSA MELALUI PERMAINAN BOLA LEMPAR KERANJANG - Suriani - Irma (Jurnal Penelitian Pendidikan Khusus, 2012)
Against the background of this research by the apparent problems in the field, the class X quadriplegic son DV / D has a low self-concept, so it does not have the confidence to perform in front umum.Penelitian aims to improve the behavior of confidence memalui quadriplegic child throwing a basket ball game . Throwing a basket ball game is a game similar to basketball games, but has been modified in accordance with the child's condition. The research methodology used was single subject research study by the research design is the design of A - B. Data analysis techniques are used based on the observed data in the form of visual analysis of graphs.